Respuesta :

2(−2 − 4p) + 2(−2p − 1) =

= -4 - 8p - 4p - 2

= -12p - 6

The expression 2(−2 − 4p) + 2(−2p − 1) is equivalent to the expression negative (2p − 1).

What is an equivalent expression?

The equivalent is the expressions that are in different forms but are equal to the same value.

Making anything easier to accomplish or comprehend, as well as making it less difficult, is the definition of simplification.

The expression is given below.

⇒ 2(−2 − 4p) + 2(−2p − 1)

Simplify the expression, then the expression will be

⇒ −2 x 2 − 4p x 2 + 2 x (−2p) − 1 x 2

⇒ −4 − 8p − 4p − 2

Simplify the expression further, then the expression will be

⇒ −8p − 4p − 2 − 4

⇒ −12p − 6

⇒ −(12p + 6)

⇒ −6(2p + 1)

Thus, the expression 2(−2 − 4p) + 2(−2p − 1) is equivalent to the expression negative (2p − 1).

More about the equivalent link is given below.

https://brainly.com/question/889935

#SPJ5

ACCESS MORE